Advances in the Determination of Nonprotein Amino Acids in Foods and Biological Samples by Capillary Electrophoresis. (3rd September 2019) - Pérez-Míguez, Raquel; Salido-Fortuna, Sandra; Castro-Puyana, María; Marina, María Luisa
Abstract: There are hundreds of nonprotein amino acids whose importance in food and biological matrices is still unknown. Many of these compounds can be found in food as products formed during the processing, as metabolic intermediates or because they are added to increase functional and nutritional properties of food. Moreover, this kind of amino acids have also demonstrated to play relevant roles in the pharmaceutical and clinical fields since they may be used therapeutically in the treatment of some pathologies and their levels may be related with some diseases. These facts imply that the analysis of nonprotein amino acids can be useful to obtain relevant information in the food and biological fields. This article reviews the most recent advances in the development of analytical methodologies employing capillary electrophoresis for the achiral and chiral analysis of nonprotein amino acids in food and biological samples. With this aim, the most relevant information concerning the separation and detection of these compounds by capillary electrophoresis is discussed and detailed experimental conditions under which their determination was achieved in food and biological samples are given covering the period of time from 2015 to 2018.